Edukasi Tui Na Massage Sebagai Upaya Pencegahan Stunting di Banyuanyar Rw 03 - Lalu Rizky S.P; Dwi Rosella K.S; Seliana Sinta D.A (Pusat Riset dan Inovasi Nasional, 2024)
Stunting is a condition of a child's lack of nutritional intake which causes growth and development disorders. Stunting has been discussed for a long time and is one of the government programs that is being sought to prevent and reduce stunting rates. One of them is education and assistance provided to the lower to middle levels of society through health institutions such as community health centers. The location of this research is UPT. The Banyuanyar Community Health Center has quite extensive facilities, including the Banyuanyar area itself up to the source. Posyandu for toddlers RW 03 is one of the built spaces. The number of children under 5 years old in the Banyuanyar RW 03 area was recorded at 24 and there were 9 children affected by stunting in the Banyuanyar area. It is hoped that the application of education and exercise therapy can prevent and reduce stunting rates. Educational activities apply interactive methods while exercise therapy uses demonstration methods. The composition of these activities includes: (1) Coordination, (2) Preparation (3) Education (4) Demonstration (5) Discussion. Based on the results of the pretest and posttest questionnaires, it was concluded that the pretest showed a lack of parental knowledge about stunting and efforts to prevent it. Meanwhile, the posttest results showed that there was a development in parents' knowledge with an average of 96% regarding the incidence of stunting and efforts to prevent it, including exercise therapy that can be applied at home